Pera+Flora+Fauna: The Story of Indigenousness and the Ownership of History @ 59th Venice Biennale (23 April–27 November 2022)—An Exhibition Review - Nicole Chang Shu Fun (Wacana Seni Journal of Arts Discourse, 2023)
Commissioned by the People of Remarkable Talents (PORT), the Perak state’s creative and cultural agency, the exhibition, entitled Pera+Flora+Fauna: The Story of Indigenousness and the Ownership of History was curated as one of the official collateral events in the 59th International Art Exhibition of La Biennale di Venezia. It highlights the local inquiries and interpretations of indigenousness, ownership of history and nature through creative expressions of contemporary artists, towards further interrogating the inter-affecting relationships between inhabitants, culture, and nature in the context of Perak state (La Biennale di Venezia 2022; Nabila 2022; PORT 2022a). Through interviews with the stakeholders involved (i.e., organising and management team, curatorial team, and participating artists), this article reviews the curation, the exhibits, and the outreach of exhibition.